91.1k views
2 votes
If 4(x-1)=8(x-2),then x=​

User Shoma
by
5.2k points

2 Answers

2 votes

Answer:

x = 3

Explanation:

4( x - 1) =8

4x - 4 = 8

+ 4 + 4

4x = 12

x = 3

8 ( x - 2 )

8 ( 3 - 2 )

24 - 16

= 8

User Harsh Patel
by
4.7k points
7 votes

4(x-1)=8(x-2)

multiply the first bracket by 4

(4)(x)=4

(4)(-1)=-4

multiply the second bracket by 8

(8)(x)=8x

(8)(-2)=-16

4x-4=8x-16

move 8x to the other side ( in other words combine like terms)

sign changes from +8x to -8x

4x-8x-4=8x-8x-16

-4x-4=-16

move -4 to the other side

-4x-4+4=-16+4

-4x=-12

divide both sides by -4 to get x by itself

-4x/-4=-12/-4

x=3

answer:

x=3

User Pypae
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.